PERAN KEPALA MADRASAH SEBAGAI PEMIMPIN PENDIDIKAN - ., Murni (Universitas Islam Negeri Alauddin Makassar, 2022)
The head of the madrasah is the regulator of the programs in the madrasa. The head of the madrasa can develop the quality of education and achievement in the madrasa in the future. In the process of improving the quality of education and achievement, the madrasa principal must have a role in improving the quality of education and achievement which can be seen from the existing vision and mission. lead the madrasa towards progress and independence. An important factor that has a big influence on the quality of education and achievement of madrasas is the head of the madrasa as an education leader. The madrasa head is the sole leader in the madrasa/school who has the responsibility to teach and influence all parties involved in educational activities to work together in achieving educational goals.